PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUTOPLAY MEDIA STUDIO 8 PADA POKOK BAHASAN ASAM BASA DI KELAS XI SMA/MA - Sintari '; Johni Azmi; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Development of interactive learning media based on Autoplay Media Studio 8 on the topic Acid Base has been done. Development of interactive learning media to get a valid, practical and effective learning media. The research method used four-D models which consists of four stages are define, design, develop and disseminate. Data collected technique used validation sheet was given to three validators (media expert and matter experts). The results showed score of the designing aspects was 3,83; pedagogic aspects was 3,80; the content aspects was 3,94; the ease of use aspects was 3,97. Average score overall validation of interactive learning media based on Autoplay Media Studio 8 on the topic Acid Base was 3,89. A valid Interactive learning media then triel used by practitioners (users), they are four teachers and 15 students from class XII MIA 3 SMAN 7 Pekanbaru and 15 students from class XII MIA 1 SMAN 12 Pekanbaru. Data analysis of learning media based on questionnaire responses of teachers and students each earned an average score of 3,79 and 94,33%. Average score overall validation and trial practitioners of learning media based on Autoplay Media Studio 8 show that this media is valid and can be use in learning process.Key Words : Interactive Learning Media, Autoplay Media Studio 8, Acid Base